Reposisi Dialektis Tafsīr Lughawī: Pergeseran Integratif Pendekatan Linguistik dalam Wacana Tafsir Kontemporer - Muhammad Naufal Hakim; Abd. Kholid (QOF, 2022)
This article aims to re-read the position of tafsīr lughawī in contemporary interpretation discourse. The background of the research is the fact that contemporary interpretation methodologies have emerged which seem to nullify linguistic reviews in interpretation. Using the critical-analytic method and the historical-philosophical approach, three points are examined: 1.) typology which includes book mapping, commentator, and interpretation methods; 2.) genealogy from its inception to its development; 3.) existential reading of tafsīr lughawī. This study infered 20 mapped tafsīr lughawī book not only use the manhaj al-lughawī but also the manhaj al-adabī, al-balāghī, and al-bayānī. The genealogy of the interpretation of the Qur’ān using a linguistic approach has existed since the time of the Prophet, the Companions, and the Tabiin, then continued until the emergence of interpretation books using lughawī style since the 2nd century Hijri. The main characteristic of tafsīr lughawī is the use of al-‘ulūm al-‘arabiyyah as the interpretating device, such as qawā‘id al-lughah (naḥw and ṣarf), ‘ulūm al-balāghah (ma‘ānī, bayān, and bādī‘), qiraah, and Jāhili Arabic poetry. In contemporary interpretation discourse, tafsīr lughawī is repositioned, in which the rules of interpretation are still used, but the lughawī style is no longer the dominant one for its integration-interconnection with other disciplines to produce a more in-depth and contextual interpretation.